Treatment effects of systematic two-stent and provisional stenting techniques in patients with complex coronary bifurcation lesions: rationale and design of a prospective, randomised and multicentre DEFINITION II trial. Issue 3 (6th March 2018) - Zhang, Jun-Jie; Gao, Xiao-Fei; Han, Ya-Ling; Kan, Jing; Tao, Ling; Ge, Zhen; Tresukosol, Damras; Lu, Shu; Ma, Li-Kun; Li, Feng; Yang, Song; Zhang, Jun; et al.
Abstract : Introduction: Provisional stenting (PS) for simple coronary bifurcation lesions is the mainstay of treatment. A systematic two-stent approach is widely used for complex bifurcation lesions (CBLs). However, a randomised comparison of PS and two-stent techniques for CBLs has never been studied. Accordingly, the present study is designed to elucidate the benefits of two-stent treatment over PS in patients with CBLs. Methods and analysis: This DEFINITION II study is a prospective, multinational, randomised, endpoint-driven trial to compare the benefits of the two-stent technique with PS for CBLs. A total of 660 patients with CBLs will be randomised in a 1:1 fashion to receive either PS or the two-stent technique. The primary endpoint is the rate of 12-month target lesion failure defined as the composite of cardiac death, target vessel myocardial infarction (MI) and clinically driven target lesion revascularisation. The major secondary endpoints include all causes of death, MI, target vessel revascularisation, in-stent restenosis, stroke and each individual component of the primary endpoints. The safety endpoint is the occurrence of definite or probable stent thrombosis. Ethics and dissemination: The study protocol and informed consent have been approved by the Institutional Review Board of Nanjing First Hospital, and accepted by each participating centre. Written informed consent was obtained from all enrolled patients. Findings of the study will be published in a peer-reviewed journal and disseminated at conferences. Trial registration number: NCT02284750 ; Pre-results.